Survey of Basic Technical Skills of Table Tennis Game Athletes Ptmsi Puslatkab Bangkalan - Khoirul Anwar; Heni Yuli Handayani; Agus Himawan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine the level of basic technical skills of table tennis athletes at PTMSI Pusat Kab Bangkalan. The method chosen and the research used a survey. Saturated samples were taken from all table tennis athletes at the Bangkalan puslatkab totaling 4 athletes. Measuring the skill level of the basic table tennis game techniques, namely Service Techniques (Serve), Attack Techniques (Attacking), Defense Techniques (Block), Drive Punch Techniques, Push Punch Techniques, Flick Techniques, and Chop Techniques for athletes at the Bangkalan sports center using tests and measurements . Researchers collected data using survey techniques with tests and measurements of basic technical skills in table tennis games for PTMSI Puslatkab Bangkalan athletes. Data analysis used percentage description. The results of the research on table tennis athletes at the Bangkalan puslatkab: basic service techniques 25% are in the adequate category and 75% are in the good category; basic attack techniques (attacking) 50% in the less category and 50% in the sufficient category; basic defense techniques (Block) 25% are in the poor category, 50% are in the sufficient category and 25% are in the good category; basic technique of hitting (Drive) 50% in the poor category, 25% in the sufficient category, and1 25% in the good category; the basic technique of push punch 75% is in sufficient category and 25% is in good category; basic technique of flick blow 25% in poor category, 50% in sufficient category, and 25% in good category; basic chop technique 75% is categorized as sufficient, and 25% is categorized as good. The conclusions of the study are the level of service technique skills (Serve) in good category, basic attack techniques (attacking) are between the less category and sufficient category, basic defense techniques (Block) are in sufficient category, basic blow techniques (Drive) are in poor category, basic techniques for push punches are categorized as enough, basic flick technique is categorized enough, and basic chop technique is categorized enough. Suggestions that can be given are the addition of hours and a proportional training program to improve mastery of the basic techniques of table tennis.